Edice Biblia Hebraica Quinta (BHQ) - Adrian Schenker (Acta Universitatis Carolinae Theologica, 2014)
The paper explains the approach applied for the edition of Biblia Hebraica Quinta (BHQ) in the context of previous critical editions of the Hebrew Bible. A concise historical survey presents the progress of the Biblical scholarship especially in the Hebrew language. It devotes more attention to the comparison of critical editions of the Hebrew Bible, in particular of Kittel’s work in the Biblia Hebraica and in the succeeding Biblia Stuttgartensia (BHS). The author justifies the adoption of the text of the Codex Leningradensis and clarifies the wider usage of sources in the critical apparatus, which differs in this way from the previous critical editions of the Hebrew Bible.